PERCENT BODY–FAT IN DIABETIC MELLITUS - MRUNALINI KANVINDE; DR.VIVEK NALGIRKAR (International Journal of Pharma and Bio Sciences, 2015)
Our purpose is to study the skinfold thickness as a useful indicator of body fat. Skinfold thickness along with percent body fat is useful indicators of obesity. The relationship between percent body-fat, serum cholesterol & blood sugar level in diabetic patients, which are found to be increased. Percent body-fat is increased in diabetic patients. As skinfold thickness has very important interrelationship serum cholesterol & blood sugar level, adiposity is main factor in hyperglycemia in diabetic patients, which is due to impaired glucose tolerance. Percent body-fat can be easily derived from triceps skinfold thickness and sub-scapular skinfold thickness. Thus increased serum cholesterol and obesity are independently related to increase skinfold thickness. This study was carried out on100 diabetic patients from civil hospital, sangli. Interrelationship between percent body-fat, derived from skinfold thickness, serum cholesterol level and blood sugar level was found out in. While carrying out this work, the socio-economic status and nutritional status was taken into consideration. In this study, the parameters included were skinfold thickness, serum cholesterol level, percent body-fat, weight, height, chest circumference and blood sugar level. Percent body-fat, derived from skinfold thickness increase in diabetic patients, with increasing age. Skinfold thickness was found in a descending order at various sites. i.e. triceps region, abdominal region, thigh region, sub-scapular region, juxta-nipple region, fore-arm region, calf of the leg and mid – axillary region. After doing statistical analysis, it was found that there is significant correlation in between percent body-fat, derived from skinfold thickness and serum cholesterol (P < 0.01). There is a close relationship was found in between percent body-fat, derived from skinfold thickness and serum cholesterol and blood sugar level, which increases with age.